2012
DOI: 10.1111/j.1524-475x.2012.00791.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the proteomic profile of chronic pressure ulcers

Abstract: Analysis of the proteomic profile of pressure ulcers over time is a critical step in the identification of biomarkers of healing or nonhealing in pressure ulcers. The wound fluid from 32 subjects with 42 pressure ulcers was evaluated over 6 weeks at 15 time points. Samples specific to both the interior and the periphery of the wound bed were collected. Antibody screening arrays, isobaric tags for relative and absolute quantitation with mass spectrometry and multiplexed microarrays were used to characterize wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 38 publications
3
48
0
Order By: Relevance
“…A proteomic analysis of chronic pressure ulcers in human patients found that MIG increases in chronic ulcers that heal but remains constant in those that do not heal. [24] …”
Section: Resultsmentioning
confidence: 99%
“…A proteomic analysis of chronic pressure ulcers in human patients found that MIG increases in chronic ulcers that heal but remains constant in those that do not heal. [24] …”
Section: Resultsmentioning
confidence: 99%
“…In pressure ulcers, chemokine (C-X-C motif) ligand 9 expression levels fail to increase as they do in healthy, healing wounds (51), leading to inhibition of endothelial cell chemotaxis at the proliferative stage of angiogenesis and subsequently aberrant angiogenesis (52). An ability to modulate the fine balance between pro- and antiangiogenic molecules might lead to novel therapeutics for induction of angiogenesis in a chronic wound.…”
Section: Wound-healing Pathologymentioning
confidence: 99%
“…Perpetuating this inflammatory state is polymicrobial infection of the wound; often with microbes capable of forming biofilms that together sustain the influx of proinflammatory cells while respectively hampering the “host response” to infection 17,1922 . Impaired angiogenesis and vasculogenesis, through aberrant regulation and cleavage of growth factors, and their receptors leads to insufficient oxygenation and inadequate delivery of nutrients to the wound 23,24 . Epidermal stem cell dysfunction due to constant cycling and subsequent depletion together with deregulated chemokines necessary to recruit bone marrow and endothelial progenitors leads to inadequate healing 11,25 .…”
Section: Introductionmentioning
confidence: 99%